Crevicular Alkaline Phosphatase Activity and Rate of Tooth Movement of Female Orthodontic Subjects under Different Continuous Force Applications - Rohaya Megat Abdul Wahab; Maryati Md Dasor; Sahidan Senafi; Asma Alhusna Abang Abdullah; Zulham Yamamoto; Abdul Aziz Jemain; Shahrul Hisham Zainal Ariffin (Hindawi Limited, 2013)
Purpose. This study is aimed to compare the effects of two different orthodontic forces on crevicular alkaline phosphatase activity, rate of tooth movement, and root resorption. Materials and Methods. Twelve female subjects of class II division 1 malocclusion participated. Maxillary canines with bonded fixed appliances acted as the tested teeth, while their antagonists with no appliances acted as the controls. Canine retraction was performed using nickel titanium coil spring that delivered forces of 100 gm or 150 gm to either side. Crevicular fluid was analyzed for ALP activity, and study models were casted to measure tooth movements. Root resorption was assessed using periapical radiographs before and after the force application. Results. ALP activity at the mesial sites peaked at week 1 for 150 gm group with significant differences when compared with the 100 gm group. Cumulative canine movements were significantly greater in the 150 gm force (2.10 ± 0.50 mm) than in the 100 gm force (1.57 ± 0.44 mm). No root resorption was in the maxillary canines after retraction. Conclusions. A force of 150 gm produced faster tooth movements and higher ALP activity compared with the 100 gm group and had no detrimental effects such as root resorption.